Rola i znaczenie pieśni religijnych w upowszechnianiu kultury muzycznej w środowisku parafialnym - Kamińska-Kłos, Beata (Studia Pastoralne, 2026)
Musical tradition of a whole church is invalueable, dominanting over other artistic forms, mainly because church singing is connected withwords (lyrics) and is an integral part of a solemn liturgy. Sacral music has evaluated togerher with the whole Roman Catholic Church for over two thousand years. To enhance the effectiveness of prayers and liturgic activitives an emotional state of its faithful is essential and a perfect goal to achieve it is to choose a suitable music. Polish dictionary defines culture as a whole achievement of humanity created in historic development or in one particular epoch. In modern ethnology and anthropology as a main factor making a culture is human activity in a general context. Ecclesial song appeared in Poland onlywhen chorale stopped being considered as an elite phenomenon. It was then that the lower classes started to participate actively in a church mess and ecclesial music gained a huge popularity. Singing in Polish slowly and with diffuculty made its way to a liturgy. Parishes, running different forms of cultural education, should provide for their believers’ needs, by professional preperations for liturgy where music andsinging is an integral and inseperable part.